Control of rat bladder neck relaxation with NORD-1, a red light-reactive nitric oxide releaser: In vitro study - Kotomi Maeda; Yuji Hotta; Naoya Ieda; Tomoya Kataoka; Hidehiko Nakagawa; Kazunori Kimura (Elsevier, 2021)
We aimed to control the relaxation of rat bladder neck specimens by using NORD-1, a red light-reactive nitric oxide (NO) releaser. Female and male 10-11-week-old Wistar/ST rats were divided into three groups: NORD-1, vehicle, and NORD-1+[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ; a soluble guanylyl cyclase inhibitor). We infused 10−4 M NORD-1 into the bladders of NORD-1 and NORD-1+ODQ group rats and the vehicle into those of vehicle group rats. Isometric tension was analyzed using circular bladder neck specimens with 10−5 M NG-nitro-l-arginine methyl ester, an NO synthase inhibitor. Moreover, 10−5 M ODQ was added into the NORD-1+ODQ group bath. After precontraction with 10−5 M carbachol, the specimens were irradiated with red light and their relaxation responses were measured. We evaluated NORD-1 tissue permeability by observing the sliced bladder neck specimens. The NORD-1 group specimens relaxed during red light irradiation; the relaxation response increased with the increase in light intensity. The vehicle and NORD-1+ODQ group specimens did not respond to irradiation. Sex-related differences in responsiveness were not noted. NORD-1 permeated into the urothelium of NORD-1 group specimens. Rat bladder neck relaxation was controlled by NORD-1 and light irradiation in vitro. NORD-1 might be a novel therapeutic agent for voiding dysfunction.